2021
DOI: 10.1177/1048291120987845
|View full text |Cite
|
Sign up to set email alerts
|

Home Care Aide Safety Concerns and Job Challenges During the COVID-19 Pandemic

Abstract: Home care aides are on the frontlines providing care to vulnerable individuals in their homes during the COVID-19 pandemic yet are often excluded from policies to protect health care workers. The goal of this study was to examine experiences of agency-employed home care aides during the COVID-19 pandemic and to identify ways to mitigate concerns. We used an innovative journaling approach with thirty-seven aides as well as in-depth interviews with fifteen aides and leadership representatives from nine home heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…When examining the results broadly, surveys of HC aides in New York [ 24 ] and Michigan [ 13 ] as well as surveys of HC agencies nationwide [ 35 , 36 ] have reported similar findings with our study. These include the lack of or difficulty sourcing PPE, concerns over transmitting or contracting COVID-19, grappling with decisions to work with increased exposure risk or face financial hardship, and accessibility issues regarding telehealth.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…When examining the results broadly, surveys of HC aides in New York [ 24 ] and Michigan [ 13 ] as well as surveys of HC agencies nationwide [ 35 , 36 ] have reported similar findings with our study. These include the lack of or difficulty sourcing PPE, concerns over transmitting or contracting COVID-19, grappling with decisions to work with increased exposure risk or face financial hardship, and accessibility issues regarding telehealth.…”
Section: Discussionsupporting
confidence: 87%
“…A qualitative analysis from a nationwide survey of HC aides ( n = 1204) found that during early weeks of the pandemic, HC aides experienced either decreased service requests from clients or requests to take on additional clients due to staffing shortages [ 11 ]. Another qualitative study using HC aide journaling and interviews identified themes related to the fear of infection and general transmission of COVID-19 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 In the home care setting, clients canceled in-home visits owing to transmission fears, and clinicians faced barriers to care provision, including a lack of access to personal protective equipment and safe transportation. [11][12][13] The COVID-19 pandemic has been particularly devastating in the nursing home setting, with high mortality rates [14][15][16] prior to vaccine distribution.…”
Section: Introductionmentioning
confidence: 99%